A variable-rate co-simulation environment for the dynamic analysis of multi-area power systems - Lopez, Claudio David; van der Meer, Arjen A.; Cvetkovic, Milos; Palensky, Peter (2017 IEEE Manchester PowerTech, 2017)
The unprecedented complexity of modern power systems has created a need for analyzing the interactions between different power system areas, which requires detailed physical models of all involved grids. However, a single institution seldom has access to enough information to build a complete model of a multi-area system. Additionally, such a model would be too labor-intensive to build and too computationally expensive to simulate. Co-simulation is an alternative that allows different institutions (TSOs, DSOs, research institutes, etc.) to simulate cooperatively by interconnecting their simulation tools, without having to disclose their grid models, and while sharing both the burden of model development and the computational load of the co-simulation. We present a co-simulation environment designed for researching the variable-rate (variable time step size) synchronization methods needed in a multi-institution setting. The environment can couple an arbitrary number of instances of DIgSILENT PowerFactory running on different virtual servers, at different rates, each representing a different area. An example use case with a three area system illustrates some of the main features of this environment. Errors bellow 5 % are evidence that this type of co-simulation is feasible, but long execution times point to additional challenges.